Rejection of pharmaceutical compounds from surface water by nanofiltration and reverse osmosis - Ana Flávia Souza Foureaux (2018)
Pharmaceutical compounds represent a diverse set of biologically active molecules used in human and veterinary medicine. The increase in the consumption of these drugs contributes to the constant occurrence of these compounds in aquatic environments.The situation is even more serious in conditions of absence of sewage treatment system.This is the case of the city of Governador Valadares, located in the state of Minas Gerais, thus discharging all its effluent to the Doce river that supplies the region. In order to guarantee the quality of water, especially for human consumption, investments in additional treatments are necessary. Among these technologies, the use of membranes, which combine the stability of the process with the excellent quality of the treatment, stands out. Thus, nanofiltration (NF) and reverse osmosis (RO) membranes were tested aiming at the pharmaceutical compounds retention in the Doce river raw water. This study was divided into three steps. In the first one, pharmaceutical compounds occurrence in all samples of the Doce river raw water was investigated. Among the pharmaceutical compounds that were found, the following stand out: Phenylbutazone and Prednisone that were rejected in 98 and 80%, respectively, by the DK membrane, whereas Betamethasone was 40.85 removed by this membrane. In addition, the efficiency of Governador Valadares central water treatment plantwas also assessed, which showed a reduction in the concentration of the pharmaceutical products in the potable water when compared to the Doce river raw water. The second part investigated five NF and two RO membranes that were tested to evaluate the physico-chemical quality and the presence of pharmaceutical compounds in permeates. Additionally, the resistance, permeability and specific energy consumption (SEC) for each membrane were assessed. It was observed a removal high efficiency of the parameters evaluated for the RO membranes, however, these membranes presented the highest resistance, energy demandand lower permeate fluxes. Dense NF membranes presented abetter set of results. The third phase refers to the choice of the best operational condition, evaluating the best transmembrane pressure and feed flow for permeates production with high quality in the physical and chemical parameters, as weel asthe drugs removal compareted with the Doce river raw water. The best operational condition obtained in the study was 10 bar of pressure and feed flow of 3.2 L/min which presented permeates flow at 45.99 L / m².h and a SEC of 0.44 KWh.m³ m²